The molecular mechanisms in prenatal drug exposure-induced fetal programmed adult cardiovascular disease - Wu, Ting; Zhou, Kaiyu; Hua, Yimin; Zhang, Wen; Li, Yifei (Frontiers in Pharmacology, 2023)
The “developmental origins of health and disease” (DOHaD) hypothesis posits that early-life environmental exposures have a lasting impact on individual’s health and permanently shape growth, structure, and metabolism. This reprogramming, which results from fetal stress, is believed to contribute to the development of adulthood cardiovascular diseases such as hypertension, coronary artery disease, heart failure, and increased susceptibility to ischemic injuries. Recent studies have shown that prenatal exposure to drugs, such as glucocorticoids, antibiotics, antidepressants, antiepileptics, and other toxins, increases the risk of adult-onset cardiovascular diseases. In addition, observational and animal experimental studies have demonstrated the association between prenatal drug exposure and the programming of cardiovascular disease in the offspring. The molecular mechanisms underlying these effects are still being explored but are thought to involve metabolism dysregulation. This review summarizes the current evidence on the relationship between prenatal drug exposure and the risk of adult cardiovascular disorders. Additionally, we present the latest insights into the molecular mechanisms that lead to programmed cardiovascular phenotypes after prenatal drug exposure.